PROCESS APPROACH IN THE MANAGEMENT OF BANKING RISKS - Tatiana Zhabotinskaya (Вестник Северо-Кавказского федерального университета, 2022)
In recent years realization in the credit organizations of the process approach providing consideration of any economic activity as a set of the interconnected business processes became one of the most demanded directions of optimization of banking business. By different estimates, from a third to a half of the Russian banks of TOP 100 already began its introduction, or plan it to make soon. However use of this approach in the sphere of risk management has a number offeatures which ignoring can reduce efficiency of the realized actions considerably. Considering it, in this article an attempt to adapt instruments of process approach to the sphere of a risk management is made.